NMR EVIDENCE FOR FORMATION OF OCTAHEDRAL AND TETRAHEDRAL AL AND REPOLYMERIZATION OF THE SI NETWORK DURING DISSOLUTION OF ALUMINOSILICATE GLASS AND CRYSTAL - Tsomaia N.; Mueller K.T.; Brantley S.L.; Hamilton J.P.; Pantano C.G. (My University, 2003)
Five sodium aluminosilicate glasses in the series Na 2O: xAl 2O 3:(3-x) SiO 2 and Na 2O:Al 2O 3:ySiO 2 were prepared and subjected to leaching at pH 2 under ambient conditions for up to 1000 h. Solid-state nuclear magnetic resonance (NMR) spectroscopy revealed the identity of aluminate and silicate environments in the leached surface layers of these glasses as well as a sample of albite crystal subjected to the same aqueous leaching. While 29Si and 27Al magic-angle spinning (MAS) NMR experiments report on the bulk structures of the samples, cross-polarization from hydrogen atoms that are present only in the surface layers provides structural information from the regions of the sample transformed during treatment. Aluminum in octahedral coordination by O atoms (Al VI) is confirmed for the first time on the near-surface region of an albite crystal under the treatment conditions of this study. A quantification of the change in the amount of six-coordinate aluminum as a function of bulk Al/Si ratio is made possible by comparing the relative amounts of 1H → 27Al CPMAS signals from Al IV and Al VI obtained from different samples under reproducible experimental conditions. The relative contribution of Al VI to total Al in the hydrated layers increases with the Al/Si ratio of the glasses studied. The leached albite crystal sample has an anomalously high concentration of Al VI given its Al/Si ratio. This anomaly is probably related to the relatively low thickness of the leached layer developed on this phase; little hydrogen penetrates the crystal surface and almost all of the Al in the thin leached layer is octahedrally coordinated, similar to Al in solution. These data suggest that hydrolysis of bridging O atoms around Al atoms in the glass or crystal hydrated layer is accompanied by a change in the coordination number of the Al atom. Aging of surfaces documents no formation of Al VI during storage after leaching. The MAS data, coupled with 27Al → 29Si CPMAS experiments, describe the bulk network structure and provide further insight into the surface structures, including documentation of repolymerization of the silicon network in the surface layer of a nepheline glass via formation of condensed Q 4 units. Further triple-resonance experiments correlate 1H, 29Si, and 27Al environments in the glasses, and indicate that the repolymerized structures in nepheline glass are not phase-separated from aluminum-containing network structures. These data for acid dissolution under ambient conditions yield the first picture of the complicated series of reactions relating connectivity and coordination number of Al and Si at the altered surfaces of geologically interesting aluminosilicates.
Keywords: Glasses